Tax Reform in Economies in Transition : A Brief Introduction to the Main Issues - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1991)
The transition from a command to a market economy requires profound reforms of the tax system. Such a transition will put downward pressures on the level of taxation at a time when public expenditure remains high. This paper outlines the main characteristics of the tax systems in centrally-planned economies. It describes recent changes in those tax systems. Finally, it discusses the major difficulties that will be faced, and the errors that must be avoided, during the transition.